SIMULASI DINAMIK PEMANFAATAN COLD STORAGE DI PELABUHAN PERIKANAN SAMUDERA BUNGUS (Jurnal Teknologi Industri Pertanian, 2023)
Padang city precisely in the administrative area of ​​Labuhan Tarok Village, Teluk Kabung Bungus District, is a capture fish production center that makes a major contribution in West Sumatera, in that area already has a cold storage which is a facility belonging to the Ministry of Maritime affairs and fisheries. Currently, the cold storage is constrained by not being used optimally, where cold storage is often found in a condition less than 50% filled. Objective of this study was to analyze the utility level of the existing cold storage using a dynamic system. In this study primary data was used by the data collection methods, namely field observations, interviews, FGD and secondary data collection derived data from relevant government agencies. The software used in this research was Vensim software. Based on the dynamic simulation obtained, it was stated that the number of fish entering cold storage generally does not show significant fluctuations. By assuming the current fleet and fishing gear, it can be concluded that if we maintain the current condition of the vessels and fishing gear, the amounts of fish caught entering cold storage will still not get the optimal cold storage capacity. Therefore, it is necessary to disseminate information to the local fishing community to empower the use of cold storage, improve the facilities and infrastructure of ocean Bungus fishery port, especially cold storage, besides that it is hoped that the local government will help find subsidized assistance for more modern fishing fleets and gear.Keywords : cold storage, dynamic simulation, fish catch